PENTINGNYA LITERASI KEUANGAN BAGI PELAJAR GENERASI Z DI KOTA PONTIANAK: PEMAHAMAN AKUNTANSI - Erwin Febriansyah; Muliawati; Nasution, Hilfa Mora Marito (UIR Press, 2025)
The rapid development of digital technology encourages the younger generation, particularly Generation Z, to acquire strong financial literacy skills in order to manage economic resources wisely amidst the fast and complex flow of information. A lack of understanding of basic accounting concepts and financial management often becomes an obstacle for students in organizing personal finances as well as in realizing the importance of simple financial record-keeping. This community service activity aimed to enhance the financial literacy of Generation Z students through the introduction of basic accounting, providing them with the ability to manage their finances in a more structured and responsible manner. The program was conducted at SMA Santo Paulus, Pontianak City, on Tuesday, September 16, 2025, using a participatory approach through interactive lectures, group discussions, and simple transaction recording simulations. These techniques were chosen to ensure that students not only understood the theory but were also able to apply basic accounting concepts in their daily lives. The results of the activity showed high enthusiasm from the participants, as reflected in their active involvement during discussions and the improvement in their understanding of financial literacy based on pre- and post-activity evaluations. This initiative is expected to foster early awareness among Generation Z students of the importance of financial management and to instill good habits in recording, organizing, and planning personal finances in a more systematic way. The rapid development of digital technology encourages the younger generation, particularly Generation Z, to acquire strong financial literacy skills in order to manage economic resources wisely amidst the fast and complex flow of information. A lack of understanding of basic accounting concepts and financial management often becomes an obstacle for students in organizing personal finances as well as in realizing the importance of simple financial record-keeping. This community service activity aimed to enhance the financial literacy of Generation Z students through the introduction of basic accounting, providing them with the ability to manage their finances in a more structured and responsible manner. The program was conducted at SMA Santo Paulus, Pontianak City, on Tuesday, September 16, 2025, using a participatory approach through interactive lectures, group discussions, and simple transaction recording simulations. These techniques were chosen to ensure that students not only understood the theory but were also able to apply basic accounting concepts in their daily lives. The results of the activity showed high enthusiasm from the participants, as reflected in their active involvement during discussions and the improvement in their understanding of financial literacy based on pre- and post-activity evaluations. This initiative is expected to foster early awareness among Generation Z students of the importance of financial management and to instill good habits in recording, organizing, and planning personal finances in a more systematic way.